A study to assess the psychological impact of fetal loss among the postnatal mothers admitted in selected hospitals of district Faridkot, Punjab, India - Bhatia, Anmol; Kaur, Bhupinder; Garg, Nishi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Miscarriage, spontaneous abortion of a fetus and the loss of an infant through stillbirth, or neonatal death is recognized as a traumatic life event before the expected point of viability. Women’s response ranges from relief to devastation. Predictors of development of complicated grief after prenatal loss include lack of social support, pre-existing relationship difficulties, or absence of surviving children, as well as ambivalent attitudes or heightened perception of the reality of the pregnancy. The study aimed to assess the psychological impact of fetal loss among the postnatal mothers. Methods: The research design selected for the study was non-experimental descriptive design. Study was conducted from Dec 2014 to Jan 2015 in obstetrics and gynaecology unit of G.G.S medical hospital, Faridkot, Punjab, India. 60 postnatal women were selected by convenience sampling. The perinatal grief scale (standardized tool) was used to assess fetal loss. Results: The majority of women i.e. 76.7% had more psychological impact, 23.3% women had less psychological impact of fetal loss. The range of score varies from 62-129 with mean score 102.82 ,SD 15.21 ,standard error mean 1.963, and median 103.50 and a statistically significant relation was found between psychological impact of fetal loss and gravida, Number of fetal loss, Number of live births and period of gestation at p<0.05. Conclusion: Hence it can be concluded that majority of women had more psychological impact of fetal loss and association of psychological impact of fetal loss was found between number of previous loss, number of live births, gravida and period of gestation.